The Role of Religious Coping, Age and Meaning in life in the Development of Post-Traumatic Growth in Egyptian Breast Cancer Survivors - Rashad, Nashwa (AUC Knowledge Fountain, 2021)
According to the World Health Organization (WHO), breast cancer (BC) is one of the most common types of cancer. Research reported survivors experienced positive changes in their relationship, strength level, and how they admired life after cancer. They said that they recognized elements that promoted post-traumatic growth, such as altering their way of life and accomplishing individually meaningful actions. This literature review reported that religious coping and meaning in life could predict post-traumatic growth. Some sources had conflicted analyses on the effect of age and education on cancer survivors and the development of PTG. This study investigates if religious coping, meaning in life, and education increase PTG and if older survivors have higher PTG than younger survivors. 147 survivors were recruited from breast cancer foundation hospital, and structured interviews were conducted with the participants over the phone. The results endorsed that religious coping and meaning are strong predictors of PTG. As for age, results indicated younger survivors reporting higher PTG than older survivors, while survivors with higher education had high PTG. It also seems that from the results, the meaning in life was the best predictor of PTG. More exploratory and qualitative research is required to understand what else can contribute to the development of PTG.